2012
DOI: 10.4172/2161-1149.1000107
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ultrasound Measurements at the Calcaneus in a Population of Urban Senegalese Women: Least Significant Difference and T-Score

Abstract: Background: Bone ultrasound measurements can be used to evaluate osteoporosis in clinical practice. As with DXA, ultrasonography shows marked variations across racial groups. In the USA, quantitative ultrasound measures were higher in African-American women than in Caucasian women. Few data are available on these measures in African women, and there are no normative data for Senegalese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Studies by Gonnelli et al and Mészáros et al indicated that both SOS and BUA can be used to distinguish between individuals with and without fractures, however, SOS seem to be somewhat more useful in men [ 54 , 55 ]. In contrast, according to a study by Ndongo et al, BUA was the most useful measure for identifying factors associated with bone status, such as age, weight and physical activity in urban Sengalese women [ 56 ].…”
Section: Bone Mineral Density (Bmd)mentioning
confidence: 99%
“…Studies by Gonnelli et al and Mészáros et al indicated that both SOS and BUA can be used to distinguish between individuals with and without fractures, however, SOS seem to be somewhat more useful in men [ 54 , 55 ]. In contrast, according to a study by Ndongo et al, BUA was the most useful measure for identifying factors associated with bone status, such as age, weight and physical activity in urban Sengalese women [ 56 ].…”
Section: Bone Mineral Density (Bmd)mentioning
confidence: 99%